Discourse on Contemporary Nepali Politics based on Class and Identity Politics - Limbu, Prem Prasad (The International Research Journal of Management Science, 2021)
The class and identity, these two factors have become major driving forces of contemporary Nepali politics. Class politics related to left political spectrum is defined as broader than identity politics. Broadly, it is believed that the left politics can support many identity question; so, identity politics can be packaged within the class politics as well. However, the contemporary Nepali politics is not in this frame where the long history of left politics is. Now, the communist party is ruling party and parallel to it the identity politics is raising in a new speed positioning as third largest political power.It has made the discourse of identity politics as an attractive agenda of discourse in Nepal. The article is completely about this new discourse of identity politics in Nepal with comparative analysis with class-based politics, its outlook and action upon identity in burning politics of Nepal. The discussion of the article isbased on the position of political parties secured in federal parliament through election, raise of the identity politics and its political agendas with some contents of class.